Regulation of osteopontin and related proteins in rat CC531 colorectal cancer cells - Georges, Rania; Adwan, Hassan; Zhivkova-Galunska, Maria; Eyol, Ergül; Bergmann, Frank; Berger, Martin R. (International journal of oncology, 2010)
Colorectal cancer accounts for 11% of all cancers and is the second most frequent cause of cancer-related death, with the majority of deaths attributable to hepatic metastasis. The main aim of the study was to investigate changes which occur in CC531 rat colon adenocarcinoma cells and are instrumental to the metastatic phenotype after homing to the liver. RT-PCR and Western blotting were used to detect the expression of certain proteins, transcription factors and enzymes, which are intimately linked to colorectal metastasis. These included osteopontin (OPN), bone sialoprotein ll (BSP ll), Runx2, Hoxc8, matrix metalloprotease-7 (MMP-7) and matrix-metalloprotease-9 (MMP-9). Subsequently, in order to detect the role of the hepatocytes in these changes seen in tumor cells, two models of co-culturing hepatocytes with CC531 cells were established. OPN, Runx2 and MMP-7 were found to be highly expressed in CC531 metastases explanted from the liver, but showed subsequent down-regulation and/or disappearance in cell culture. The inverse regulation of Hoxc8, OPN and Runx2 suggests that these genes may be regulated in a feed-back loop manner. MMP-9 mRNA and active MMP-7 protein were expressed in tumor cells themselves. The presence of hepatocytes was insufficient to induce induction of OPN and Runx2 in tumor cells in vitro, so was the addition of OPN or TGF-β1. Whereas TGF-β1 induced over-expression of OPN and Runx2 in hepatocytes, it did not exert the same effect on hepatocytes co-cultured with CC531 cells, indicating that this response was abrogated by CC531 cells.